The yeasts a taxonomic study - Kurtzman, C. P.; Fell, Jack W.; Boekhout, T. (Elsevier, 2010)
Fully revised, updated and offered in a new two-volume format, The Yeasts: A Taxonomic Study, 5th Edition remains the most comprehensive presentation of yeast taxonomy and systematics available. Nearly 1500 species of ascomycete and basidiomycete yeasts are included, each description offering not only standard morphological and physiological characters, but also information on systematics, habitat, ecology, agricultural and biotechnological applications and clinical importance. Extensive introductory chapters discuss clinical aspects of yeasts, their role in biotechnology, food and beverage spoilage, agriculture and ecology, while other chapters include methodology for isolation of species from various habitats, phenotypic characterization, chemotaxonomy, gene sequence analysis and phylogenetics, including whole genome analysis. Additionally, easy-to-understand trees illustrate the phylogenetic placement of each species in its assigned genus as they have been determined from gene sequence analysis. This essential work, prepared by the leading experts in the field, is the most definitive treatment of taxonomy and systematics of yeasts on the market, and a necessary reference for any bookshelf or workbench. High quality photomicrographs and line drawings enhance world-class content Detailed trees clearly illustrate phylogenetic placement of each species in its assigned genus Discussion of clinical aspects of yeasts, including their role in biotechnology, agriculture and ecology help contextualize content for a wide range of researchers.
Keywords: kvasinky; systematická botanika; Saccharomycetales; systematic botany; elektronické knihy; electronic books